PEMBELAJARAN IPS DENGAN PENDEKATAN INTERDISIPLINARITAS - Sujarwo, Sujarwo; Ciciria, Deri (LPPM STKIP PGRI Bandar Lampung, 2019)
This reseach aims to get an overview of learning Social Studies with an interdisciplinarity approach at the Junior High School in Bojong Gede Kabupaten Bogor. This research was conducted qualitatively by trying to discover the implementation of social studies learning in an interdisciplinary by means of an interview, observation, observation the documentation and literature review. Based on the reseach done known that the implementation of social studies learning with an interdisciplinarity approach consists of three aspects, first learning planning, the second implementation of learning and the third evaluation of learning. In the planning stage, the steps taken are; 1) review and analyze standards of competence / core competencies and basic competencies, 2) set the themes, 3) map basic competencies and indicators of material achievement, 4) create theme networks, 4) develop thematic syllabus and 5) compossing lesson plans thematic. At the stage of the implementation of social studies learning with an interdisciplinarity approach can be done by submitting material in an integrated manner based on predetermined themes. The choice of themes in the interdisciplinarity approach can be done by analyzing basic competencies, then determining the theme based on the main topic, based on the main potential and based on the problem, so that the boundaries between one discipline and another become invisible and manifest interdisciplinarity between social studies. At the stage of evaluation of social studies learning with interdisciplinarity is to measure indicators of achievement of competencies that cover three aspects of the domain in accordance with the objectives of social sstudies, namely aspects of skill and values.